2020
DOI: 10.1016/j.celrep.2020.107652
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Epigenetic Suppression of Muscle Stem Cell Necroptosis Is Required for Efficient Regeneration of Dystrophic Muscles

Abstract: Highlights d Necroptotic cell death of MuSCs is essential for efficient muscle regeneration d Inhibition of necroptosis exacerbates adverse crosstalk among mdx muscle stem cells d The CHD4/NuRD complex directly represses Ripk3dependent necroptosis d Attenuated recruitment of CHD4 to Ripk3 locus lowers necroptosis threshold in dystrophy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 84 publications
2
28
2
Order By: Relevance
“…In vivo, the total SC numbers were equivalent between WT and Tam-CRE CHD4 mKO mice. This is in disagreement with a recent study that showed a reduced number of SCs in the CHD4 KO 13 , which could be explained by the partial KO of the CHD4 protein we obseve in our study following tamoxifen administration. Histologically, no differences were noted between the TA muscle fibers from Tam-CRE CHD4 mKO mice compared to WT mice (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In vivo, the total SC numbers were equivalent between WT and Tam-CRE CHD4 mKO mice. This is in disagreement with a recent study that showed a reduced number of SCs in the CHD4 KO 13 , which could be explained by the partial KO of the CHD4 protein we obseve in our study following tamoxifen administration. Histologically, no differences were noted between the TA muscle fibers from Tam-CRE CHD4 mKO mice compared to WT mice (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…The combination of GDF11 upregulation along with downregulation of Wnt signaling suggests that the intercostal and back muscle abnormalities in CHD4 KO embryos could be mediated, in part, by perturbing these pathways. A recent study showed that deletion of CHD4 in adult muscle stem cells leads to increased expression of Ripk3, which mediates satellite cells necroptosis 13 . Our RNA-Seq data did not reveal upregulation of Ripk3 in E18.5 CHD4mKO muscles suggesting that CHD4-induced Ripk3 suppression is not required for muscle stem cells proliferation and differentiation during muscle development.…”
Section: Conditional Deletion Of Chd4 In Adult Scs Disrupts Muscle Rementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in chronic muscle degenerative disease (Duchenne Muscular Dystrophy, DMD) as previously reported, whether myofibers commit to progressive necroptosis is still controversial. 58,59 Moreover, a subset of noncompetitive MuSCs were found to undergo necroptosis in the mdx mice; no MuSC necroptosis was observed in wild type mice after CTX-induced acute injury. 59 These findings suggested that necroptosis engages in both acute and chronic muscle regeneration, but play different roles depending on the contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The activity and stability of RIPK3 are controlled by caspase-dependent cleavage and by various post-translational modifications, including phosphorylation, ubiquitination, and glycosylation [13][14][15][16]. However, little is known about the transcriptional regulation of Ripk3 in any cell type, other than its repression by CHD4 and by hypoxia-inducible factor 1 (HIF-1) in hypoxic ECs [10], its repression by CHD4 in muscle stem cells [17], and its methylationdependent repression and promotion by the transcription factor SP1 in tumor cells [18,19]. Therefore, we sought to identify transcriptional regulators of Ripk3 in this study, and we chose to perform our screen in ECs because of our interest in the detrimental impact of misregulated RIPK3 expression on embryonic and postnatal vasculature.…”
Section: Introductionmentioning
confidence: 99%